Reconstruction of The Concept Of Islamic Education; Weighing Offers Syed Muhammad Nuquib Al-Attas - Nur Khasanah; Havis Aravik; Achmad Irwan Hamzani (Institut Agama Islam Al-Quran Al-Ittifaqiah (IAIQI) Indralaya, 2023)
Muhammad Naguib Attas' educational thinking is unique because apart from being based on the values contained in Islam, he also understands the development of Islamic education through linguistic analysis. The concept of Islamic education is widely discussed, but it is not an old topic that is worth discussing. The development of the times is becoming more rapid day by day, especially in the context of liberalization and secularization of modern ideological currents, so scientists' thoughts need to be integrated with current educational concepts. Sayyid Naquib Al-Attas was an Indonesian Muslim scientist whose ideas made a significant contribution to Islamic education. The approach to this research uses a qualitative approach, with the type of library research. The data sources for the research were obtained from journals related to research, books, and electronic media. The results of this research show that Islamic education is the equivalent of the term al-ta'dib which according to him is suitable to be used as a term in Islamic education because the concept of ta'dib was what the Prophet Muhammad taught his people in the past.